Diastolic Function Assessment by Echocardiography at Dhulilkhel Hospital - Humagain, Sanjaya; Koju, Rajendra Prasad (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Diastolic dysfunction (DD) is understood as impaired Left ventricular relaxation. Echocardiography is the key in diagnosis. In 2016 recommendation by American Society of Echocardiography(ASE) and the European Association of Cardiovascular Imaging (EACVI) was updated. In our country we do not have a general consensus. Diastolic dysfunction is reported on the basis of E/A ratio of mitral flow, that has the chance of missing a lot of patients with pseudo-normalization. This study carried out to look at importance of evaluation of other parameters to diagnose a patient with diastolic dysfunction. Methods: It is a retrospective cross-sectional descriptive study. Echocardiography report from the year 2018 and 2019 was collected from database and the patients with diagnosis of Diastolic dysfunction were selected. Patient profile and the echocardiographic parameter were recorded. Echocardiography was reported according to 2016 ASE and EACVI update. Results: Total of 1982 patients selected for analysis. E/A < 0.8 was seen in 702(35.4%) patients, E/A 0.8- 2.0 was seen in 1136 (57.3%) patients and E/A > 2.0 was found in 144(7.3%) patients. The most common finding being E/e’ 1470 (74.2%) of patients followed by TR velocity > 2.8m/s 1422 (71.7%), Septal e’ velocity < 7 cm/s or Lateral e’ velocity <10 cm/s 1334 (67.3%) and LA area >20 cm2 1286 (64.8%) respectively. Conclusions: Diastolic dysfunction should be evaluated using all the parameters recommended by 2016 ASE and EACVI guideline update. Measurement of only E/A ratio has a chance of missing large number of patient with DD.